A Comparative Study: Superficial Shaving Combined With Photodynamic Therapy Versus Cryotherapy in the Treatment of Recalcitrant Plantar Warts. Issue 8 (10th January 2020) - Huang, Kai; Xie, Yang; Li, Mingjia; Liu, Dihui; Su, Juan; Li, Fangfang; Deng, Bo; Li, Jie; Shi, Wei; Zhang, Jianglin; Chen, Xiang; Zhao, Shuang; et al.
Abstract : Background and Objectives: Plantar warts are a viral infectious lesion on the foot. The regression of plantar warts can be challenging despite the presence of a variety of available treatment modalities. Photodynamic therapy (PDT) has been recommended for the treatment of plantar warts. However, the effect of PDT in the treatment of plantar warts is not clear. Thus, we compared the efficacy of combining superficial shaving with PDT (SS‐PDT) with that of cryotherapy in the treatment of recalcitrant plantar warts. Study Design/Materials and Methods: Forty‐six patients with 271 warts received SS‐PDT, and 26 patients with 147 warts received cryotherapy. For the SS‐PDT group, the lesions were shaved in situ, and PDT was performed immediately. For the cryotherapy group, appropriate pressure was applied by freezing rod to fully freeze the lesion tissue. The overall clinical response effects, recurrence rates, adverse events, patient satisfaction and the quality of life were assessed. Results: The SS‐PDT group achieved a 91.3% success rate (defined as >50% on clearance) after treatment for 6 months, whereas only 23.1% of treatment in the cryotherapy group was successful. After 6 months of follow‐up, the recurrence rate in the SS‐PDT group was significantly lower than that in the cryotherapy group (8.7% vs. 76.9%, P < 0.001). The patients with SS‐PDT were more satisfied with the treatment than the patients with cryotherapy (8.8 ± 1.4 vs. 4.9 ± 1.4, P < 0.001). Moderate pain was the main adverse event in SS‐PDT, and cryotherapy may cause severe pain and blistering. Conclusions: Our results suggest that superficial shaving combined with PDT is promising as a safe and effective therapy for patients with plantar warts, especially for patients with multiple recalcitrant warts. Lasers Surg. Med. © 2020 Wiley Periodicals, Inc.